Epstein-Barr-positive classical Hodgkin lymphoma-associated haemophagocytic lymphohistocytiosis: a rare case. (14th August 2018) - Iardino, Alfredo; Amar, Zain; Ahmed, Yasir
Abstract : Haemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition, which is usually triggered by autoimmune disorders, viral infections and malignancy, like lymphomas. We present a 60-year-old Hispanic woman with a medical history of hypertension and systemic lupus erythematosus presenting with fever, generalised weakness and shortness of breath for 3 weeks. She was hypotensive on presentation, and a CT scan of abdomen/chest showed multiple irregular hepatic and splenic hypodense lesions. A liver biopsy revealed Classical Hodgkin lymphoma (cHL) with positive Epstein-Barr virus (EBV) staining that was later confirmed with high serum EBV DNA levels. Incidentally, a liver biopsy disclosed haemophagocytosis in some cells. HLH-associated cHL is an uncommon condition that can cause severe systemic symptoms acting as the perfect mimic of septic shock, deviating the clinical eye toward treating with antibiotics and not addressing in a timely manner the real aetiology of the patient's condition.